2018
DOI: 10.3892/ol.2018.9575
|View full text |Cite
|
Sign up to set email alerts
|

Rhamnetin induces apoptosis in human breast cancer cells via the miR‑34a/Notch‑1 signaling pathway

Abstract: The present study aimed to investigate whether rhamnetin induced apoptosis in human breast cancer cells and the underlying molecular mechanism of this anti cancer effect. The treatment of MCF-7 cells with rhamnetin was able to significantly inhibit cell proliferation and induce caspase-3/9 activity in a dose-and time-dependent manner, compared with untreated cells. In addition, treatment with rhamnetin was able to significantly promote the expression of p53 protein and microRNA (miR-)34a compared with untreate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 37 publications
0
28
0
Order By: Relevance
“…Meanwhile, OC contains a high amount of chlorophyll (Park & Park, 1998), and chlorophyll can be degraded into grey‐brown compounds such as pheophorbide and pheophytin (Heaton & Marangoni, 1996). In addition, a recent study revealed that rhamnetin can induce apoptosis in human breast cancer cells (Lan et al., 2019). Moreover, isorhamnetin was reported to exhibit anti‐proliferative and pro‐apoptotic effects in AGS human gastric cancer cells (Ramachandran et al., 2012), and Somerset and Johannot (2008) reported that pear is the main source of isorhamnetin in adult Australian population.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, OC contains a high amount of chlorophyll (Park & Park, 1998), and chlorophyll can be degraded into grey‐brown compounds such as pheophorbide and pheophytin (Heaton & Marangoni, 1996). In addition, a recent study revealed that rhamnetin can induce apoptosis in human breast cancer cells (Lan et al., 2019). Moreover, isorhamnetin was reported to exhibit anti‐proliferative and pro‐apoptotic effects in AGS human gastric cancer cells (Ramachandran et al., 2012), and Somerset and Johannot (2008) reported that pear is the main source of isorhamnetin in adult Australian population.…”
Section: Discussionmentioning
confidence: 99%
“…miR-34a has been demonstrated to function as an important tumor suppressor by regulating a variety of tumor progression steps, including cell proliferation, invasion and apoptosis, and Notch, which is a target gene of miR-34a (142). In metastatic breast cancer cells, overexpression of miR-34a significantly increases the protein level of tumor suppressor gene p53 and decreases the expression of Notch1, thereby inhibiting cell proliferation, invasion and inducing apoptosis (143,144). Additionally, miR-34a can sensitize metastatic breast cancer cells to paclitaxel and adriamycin (chemotherapeutic drugs for breast cancer) partly by downregulating Notch1 expression (142,145).…”
Section: Notch-associated Micrornas In Breast Cancer Metastasismentioning
confidence: 99%
“…Scientists are interested in derivatives of quercetin such as rhamnetin that modulates miR-34a in different cell lines [87][88][89] . Finally, we found an article, which reversed the usual logic.…”
Section: Quercetin Glycosides and Its Derivativesmentioning
confidence: 99%